(untitled) (Revista Contexto & Saúde, 2026)
Objective: To analyze the sociodemographic and clinical profile of pregnant women with use, misuse, or dependence on drugs of abuse and of their newborns, comparing these characteristics before and during the COVID-19 pandemic. Methods: A descriptive cross-sectional study based on secondary data extracted from the medical records of pregnant women with substance use disorders treated at a high-complexity health center in the Central-West region of Minas Gerais, Brazil, between March 2019 and March 2021. Results: A total of 52 medical records were analyzed. Among the documented psychoactive substances, tobacco was the most frequent (69.3%), followed by alcohol (43.1%), marijuana (40.8%), and cocaine (35.4%). The simultaneous use of two or more substances was common, particularly the combination of alcohol + tobacco (21.0%). Comorbidities were frequent, especially syphilis (28.1%), urinary tract infection (21.9%), and hypertension (21.9%). Among the newborns, 19.6% were preterm, and the median gestational age was 38 weeks; 12.2% had low birth weight. There were no statistically significant differences between pregnant women evaluated before (n = 18) and during (n = 34) the pandemic regarding sociodemographic characteristics, clinical profile, substance use patterns, or neonatal outcomes. Conclusion: The findings reinforce the need for public health strategies targeted at the care of pregnant women who use psychoactive substances, in order to reduce associated risks to maternal and neonatal health.